Mechanical behavior of SiC reinforced ZA63 Mg matrix composites: Experiments and 3D finite element modelling - Chong Wang; Zelong Du; Enyu Guo; Shuying Bai; Zongning Chen; Huijun Kang; Guohao Du; Yanling Xue; Tongmin Wang (Journal of Magnesium and Alloys)
In this work, the microstructure evolution and mechanical behavior of extruded SiC/ZA63 Mg matrix composites are investigated via combined experimental study and three-dimensional finite element modelling (3D FEM) based on the actual 3D microstructure achieved by synchrotron tomography. The results show that the average grain size of composite increases from 0.57 µm of 8 µm-SiC/ZA63 to 8.73 µm of 50 µm-SiC/ZA63. The type of texture transforms from the typical fiber texture in 8 µm-SiC/ZA63 to intense basal texture in 50 µm-SiC/ZA63 composite and the intensity of texture increases sharply with increase of SiC particle size. The dynamic recrystallization (DRX) mechanism is also changed with increasing SiC particle size. Experimental and simulation results verify that the strength and elongation both decrease with increase of SiC particle size. The 8 µm-SiC/ZA63 composite possesses the optimal mechanical property with yield strength (YS) of 383 MPa, ultimate tensile strength (UTS) of 424 MPa and elongation of 6.3%. The outstanding mechanical property is attributed to the ultrafine grain size, high-density precipitates and dislocation, good loading transfer effect and the interface bonding between SiC and matrix, as well as the weakened basal texture. The simulation results reveal that the micro-cracks tend to initiate at the interface between SiC and matrix, and then propagate along the interface between particle and Mg matrix or at the high strain and stress regions, and further connect with other micro-cracks. The main fracture mechanism in 8 µm-SiC/ZA63 composite is ductile damage of matrix and interfacial debonding. With the increase of particle size, interface strength and particle strength decrease, and interface debonding and particle rupture become the main fracture mechanism in the 30 µm- and 50 µm-SiC/ZA63 composites.